Short- versus prolonged-course antibiotic therapy for sepsis or infectious diseases in critically ill adults: a systematic review and meta-analysis. Issue 3 (4th March 2022) - Kubo, Kenji; Kondo, Yutaka; Yoshimura, Jumpei; Kikutani, Kazuya; Shime, Nobuaki
Abstract: Background: The 2016 International Guidelines for the Management of Sepsis and Septic Shock recommend antibiotic therapy for 7–10 days for most patients with sepsis. However, evidence on critically ill patients is limited. Thus, we conducted the first systematic review and meta-analysis comparing the effectiveness and adverse events of shorter- (≤1 week) with longer-course antibiotics in adults with critical infections including sepsis. Methods: We searched the MEDLINE, Cochrane Central Register of Controlled Trials, and Igaku Chuo Zasshi databases for randomised controlled trials (RCTs) and observational studies (OSs) from inception to 31 March 2021. Results: We included 6 of 3, 766 identified articles, incorporating data from 4 RCTs and 2 OSs (1, 721 patients) in meta-analyses. Three RCTs and one OS focussed on ventilator-associated pneumonia, and one RCT and one OS investigated intra-abdominal infections. The severity score levels were similar to that of sepsis, but no study comprehensively focussing on sepsis was found. There were no significant differences in mortality at a maximum follow-up of 30 days (RR 1.08, 95%CI 0.80–1.46); 28-day mortality, clinical cure, the occurrence of new events, and the emergence of resistant organisms between the groups in the RCTs. The OSs findings were consistent. The quality of evidence was assessed as very low to moderate using the GRADE approach, with no uniform description of severity scores, sepsis, or adverse events. Conclusions: Shorter, fixed-duration antibiotic therapy for clinically heterogeneous sepsis or severe infections was not associated with poorer outcomes, but the overall quality of evidence was poor.